Unveiling Squamous Papilloma Resembling Verruca Vulgaris in a Case of Nevus Sebaceous: A Diagnostic Challenge - Debasmita Behera; Farheen Begum; Chinmoy Raj; Shini Choubey (Wolters Kluwer Medknow Publications, 2024)
This case report details the unusual presentation of a 6-year-old male child who had an asymptomatic, well-defined, brown raised lesion over the vertex area of the scalp since birth. His parents noticed a new growth with finger-like projections over existing old lesions for 1 year. With an initial diagnosis of growth of verruca over nevus sebaceous (NS), a sample for histopathology study was sent which revealed findings consistent with squamous papilloma occurring on NS. This is reported to emphasize that any growth over NS should be confirmed histopathologically due to the rarity of this association and to reduce the possibility of its malignant potential. The article emphasizes how crucial histological analysis is to clarifying mistaken cutaneous lesions and refining an accurate diagnosis.